Cardiovascular complications of diabetes mellitus in sub-Saharan Africa - Kengne, A.P.; Amoah, A.G.; Mbanya, J.C. (Circulation, 2005)
Background - Cardiovascular disease, the major cause of mortality and morbidity in modern societies, is set to overtake infectious diseases in the developing world as the most common cause of death. The increasing prevalence of major and emerging cardiovascular risk factors accounts for the growing burden of cardiovascular disease in the world. Diabetes in all its forms is one of the main cardiovascular risk factors. Two of 3 diabetic patients will die as a result of cardiovascular complications, and approximately 30% of patients treated in cardiovascular intensive care units have diabetes. Methods and Results - This review on the cardiovascular complications of diabetes in sub-Saharan Africa is a bibliographical MEDLINE search of published data over the past 2 decades. Diabetes-related cardiovascular disease complications are considered to be rare in Africa but are on the rise and are regularly associated with classic cardiovascular risk factors. Coronary heart disease may affect 5% to 8% of type 2 diabetic patients and cardiomyopathy, up to 50% of all patients. Close to 15% of patients with stroke have diabetes, and up to 5% of diabetic patients present with cerebrovascular accidents at diagnosis. Peripheral vascular disease prevalence varies across sites from 4% to 28%. Conclusions - It is obvious that diabetes mellitus and related cardiovascular complications are gaining more importance in sub-Saharan Africa. The relative contribution of putative risk factors is not well defined, and further research is therefore needed. © 2005 American Heart Association, Inc.
Keywords: Africa, south of the Sahara; Cardiovascular diseases; Complications; Diabetes mellitus